2011
DOI: 10.1017/s0007114511002935
|View full text |Cite
|
Sign up to set email alerts
|

Rumen protozoa and methanogenesis: not a simple cause–effect relationship

Abstract: Understanding the interactions between hydrogen producers and consumers in the rumen ecosystem is important for ruminant production and methane mitigation. The present study explored the relationships between rumen protozoa, methanogens and fermentation characteristics. A total of six donor sheep harbouring (F, faunated) or not (D, defaunated) protozoa in their rumens (D animals were kept without protozoa for a period of a few months (D2) or for more than 2 years (Dþ)) were used in in vitro and in vivo experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
107
2
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 50 publications
16
107
2
6
Order By: Relevance
“…The relationship between rumen methanogen abundance and methanogenesis is less clear when changes in enteric CH 4 emissions are modulated by diet or are a consequence of selecting phenotypes related to feed efficiency or MeY. Whereas in some reports, significant positive relationships were identified (Aguinaga Casañas et al, 2015;Arndt et al, 2015;Sun et al, 2015;Wallace et al, 2015), in many others, the concentration of methanogens was unrelated to methanogenesis (e.g., Morgavi et al, 2012;Kittelmann et al, 2014;Shi et al, 2014;Bouchard et al, 2015). Bouchard et al (2015) even reported a reduction in methanogens without a significant decrease in MeP for steers fed sainfoin silage.…”
Section: Rumen Function Metabolites and Microbiomementioning
confidence: 99%
“…The relationship between rumen methanogen abundance and methanogenesis is less clear when changes in enteric CH 4 emissions are modulated by diet or are a consequence of selecting phenotypes related to feed efficiency or MeY. Whereas in some reports, significant positive relationships were identified (Aguinaga Casañas et al, 2015;Arndt et al, 2015;Sun et al, 2015;Wallace et al, 2015), in many others, the concentration of methanogens was unrelated to methanogenesis (e.g., Morgavi et al, 2012;Kittelmann et al, 2014;Shi et al, 2014;Bouchard et al, 2015). Bouchard et al (2015) even reported a reduction in methanogens without a significant decrease in MeP for steers fed sainfoin silage.…”
Section: Rumen Function Metabolites and Microbiomementioning
confidence: 99%
“…In addition, the genome sequence of the common rumen methanogen, Methanobrevibacter ruminantium, is available (Leahy et al, 2010) and sequencing of the genomes of other rumen methanogens is under way (see 'Rumen methanogen genome sequencing projects subsection'). However, in spite of all this information, methanogenesis in the rumen cannot be correlated to the number of methanogens (Yanez-Ruiz et al, 2008;Mosoni et al, 2011;Popova et al, 2011) or unequivocally assigned to a particular community structure Morgavi et al, 2012). Methane production is intimately associated with the concentration of hydrogen and the interactions of methanogens with other microbes producing and consuming hydrogen in the rumen (Janssen, 2010;Morgavi et al, 2010).…”
Section: The Ruminant Superorganismmentioning
confidence: 99%
“…Some in vitro and in vivo studies demonstrated that the lack of the protozoal population in the rumen ecosystem has a significant effect on both the population of methanogens and the level of methane production (Cieslak et al, 2009a;Morgavi et al, 2012). The research also showed that sheep maintained without protozoa for more than 2 years have reduced methanogenesis in comparison with sheep kept without protozoa for only 2 months .…”
Section: Characteristics Of the Rumen Ecosystem In Relation To Methanmentioning
confidence: 99%